Letter from Bullock & Crenshaw to James Curtis Booth - Bullock & Crenshaw (1860)
Bullock & Crenshaw, a wholesale drug firm founded in 1849, writes to James Curtis Booth (1810-1888) concerning a Mint balance.
Keywords: Booth, James Curtis, 1810-1888; Mint of the United States; United States Mint